2013
DOI: 10.3904/kjim.2013.28.4.420
|View full text |Cite
|
Sign up to set email alerts
|

The dose of cyclophosphamide for treating paraquat-induced rat lung injury

Abstract: Background/AimsCyclophosphamide (CP) is a promising treatment for severe cases of paraquat (PQ) poisoning. We investigated the effective dose of CP for mitigating PQ-induced lung injury.MethodsAdult male Sprague-Dawley rats were allocated into five groups: control, PQ (35 mg/kg, intraperitoneal injection), and PQ + CP (1.5, 15, or 30 mg/kg). The dimensions of lung lesions were determined using X-ray microtomography (micro-CT), and histological changes and cytokine levels were recorded.ResultsThe micro-CT resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Furthermore, reduced MPO activity was also detected in a mouse model of bleomycin induced‐pulmonary toxicity that was treated with silymarin . The present study demonstrates that PQ administration caused lung histopathological changes, including infiltration of inflammatory cells, thickening of alveolar septum and collagen accumulation, which are in line with previous findings . However, our experiments revealed that lung injury and inflammatory responses (the infiltration of neutrophils and macrophages) in lung tissue were effectively alleviated by silymarin administration.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, reduced MPO activity was also detected in a mouse model of bleomycin induced‐pulmonary toxicity that was treated with silymarin . The present study demonstrates that PQ administration caused lung histopathological changes, including infiltration of inflammatory cells, thickening of alveolar septum and collagen accumulation, which are in line with previous findings . However, our experiments revealed that lung injury and inflammatory responses (the infiltration of neutrophils and macrophages) in lung tissue were effectively alleviated by silymarin administration.…”
Section: Discussionsupporting
confidence: 92%
“…PQ intoxication leads to ALI within few days which involves neutrophil influx, alveolar hemorrhage and edema of pulmonary epithelial cells. Till date, no effective drug is available to prevent PQ-induced lung damage although some studies have suggested that immunosuppressive agents such as methylprednisolone and cyclophosphamide may be effective (Zerin et al, 2012;Choi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The lungs are the main target organs of paraquat, leading to severe injury and fibrosis, causing epithelial cellular injury due to your action on type I and type II pneumocytes in addition to edema, hemorrhage, infiltration of inflammatory cells and cellular espações (Rocco et al, 2004;Samson et al, 2006;Choi et al, 2013), however, the oxidative stress plays a crucial role in the pathogenesis of paraquat-induced lung injury (Tian et al, 2014).…”
Section: Fig1chemical Structure Of Paraquatmentioning
confidence: 99%